2022
DOI: 10.1108/qrfm-07-2021-0115
|View full text |Cite
|
Sign up to set email alerts
|

Identifying salient beliefs underlying intention to save regularly: an elicitation study of Malaysian Gen Y

Abstract: Purpose Using the integrated behavioural model as a theoretical framework, this study aims to identify salient beliefs underlying intention to save regularly among Gen Ys in Malaysia. Design/methodology/approach Semi-structured interviews were conducted with 13 participants who were selected using purposive and snowball sampling methods. Findings While Gen Ys are not pushed by others to save, they find that older people (parents, parents-in-law, colleagues and relatives) influence them to save. The main fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…However, Duflo & Saez (2003) explained the influence of peers in maintaining saving decisions. Lopez, Mahdzan, & Rahman (2022) determined that only older or close friends advised participants to save-not friends of the same age. Peer groups have maximum influence during adolescence because young adolescents have less knowledge and are uncertain about making decisions (Zulfaris et al, 2020).…”
Section: Theoretical Framework and Empirical Studiesmentioning
confidence: 99%
“…However, Duflo & Saez (2003) explained the influence of peers in maintaining saving decisions. Lopez, Mahdzan, & Rahman (2022) determined that only older or close friends advised participants to save-not friends of the same age. Peer groups have maximum influence during adolescence because young adolescents have less knowledge and are uncertain about making decisions (Zulfaris et al, 2020).…”
Section: Theoretical Framework and Empirical Studiesmentioning
confidence: 99%
“…, 2016) – could have influenced their instrumental attitude towards saving. Low financial commitments may influence levels of perceived control (Lopez et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…As most respondents in this study held at least a bachelor's degree, their higher level of cognitive abilitywhich is required for financial literacy (Muñoz-Murillo et al, 2020;French and McKillop, 2016;Farrell et al, 2016) could have influenced their instrumental attitude towards saving. Low financial commitments may influence levels of perceived control (Lopez et al, 2023). Based on the demographics of the respondents in this study, in which younger Gen Ys were over-represented compared to older Gen Ys, an inference could be madethis age group is likely to be single, stay with their parents, and have relatively fewer financial commitments, and thus have greater control over their decisions to save.…”
Section: Saving Behavior Determinants Of Gen Ymentioning
confidence: 94%
“…Savings is an essential element. However, the study carried out by the Department of Statistics Malaysia in March found that Malaysian savings will only last between one to four months, especially during the COVID-19 pandemic (Goh, 2020;Lopez et al, 2022;Nizar et al, 2021). This shows that Malaysians do not save enough as their savings awareness is still lacking.…”
Section: Unstable Incomementioning
confidence: 99%